The Effectiveness of the Berjaya Farmer Card in Helping the Provision of Fertilizer for Farmers in North Lampung - Marhaeni (International Journal of Economics, Business, and Entrepreneurship, 2024)
The successful farmer card program was initiated by the Lampung Regional Government. One of the successful farmer card programs is to streamline the distribution of subsidized fertilizer with the aim that only small farmers are the targets of this subsidy/assistance. The business fields that have a major influence on the economic structure of Lampung Province are Agriculture, Forestry, and Fisheries; as well as the Processing Industry. This research was carried out at the Plentis Tani Kiosk and Integrated Kiosk in Mersi, which is located at Jl. Senopati No. 78 Arcawinangun, Semuli Jaya, North Lampung Regency. The results of the research show that there is a difference in the effectiveness of the distribution of subsidized fertilizer using Tani Berjaya cards and the effectiveness of the distribution of subsidized fertilizer without Tani Berjaya cards. The distribution of subsidized fertilizer using the farmer card pattern based on the six right principles is quite effective. In detail, the effectiveness of distribution of subsidized fertilizer using the farmer card pattern in terms of right price, right place, right time, right quality, and right type is classified as ineffective. The distribution of subsidized fertilizer using the Berjaya Farmer Card pattern, in terms of the exact amount, is classified as ineffective.